Pregnancy outcome in cases of rupture uterus: a clinical study - Kalewad, Pallavi S.; Bava, Amarjeet; Nandanwar, Y. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the study was to evaluate and analyze the risk factors, maternal and perinatal outcome in cases of ruptured uterus. Methods: It is retrospective observational study was designed from January 2015 to December 2015. A total of 69 patients diagnosed with ruptured uterus during the study period were included. Results: The incidence of uterine rupture was 0.64%. The uterine rupture in scarred uterus seen in 66 (95.6%) cases and unscarred uterus 3 (4.4%) cases. Forty five (65.3%) patients did not receive any antenatal care. Sixty six (49.1%) of the cases underwent previous uterine surgery due to cesarean. Other observed predisposing factors were induced/augmented labor seen in 39 cases (29.1%), prolonged labor in 8 (6%), macrosomic fetus 8 (11.6%), grand multiparous 10 (7.5%), multiple pregnancies 4 (3%) and malformed baby 2 (1.5%), cephalopelvic disproportion 2 (1.5%), instrumental deliveries 1 (0.7%) respectively. Primary repair of uterus was performed in 52 (75.2%) of the patients. Subtotal abdominal hysterectomy was performed in 10 patients (15.2%). There were seven fetal deaths and two maternal deaths recorded during the study period. Conclusions: Uterine rupture is a major contributing factor for maternal and perinatal morbidity and mortality. Proper antenatal care and early referral of women at risk to tertiary center will significantly improve maternal and perinatal outcome. Uterine rupture is amongst the preventable obstetric complication that carries severe risks both to the mother as well as the baby. Health education of people, training and supervision of health personal will reduce incidence especially in remote areas.